2011
DOI: 10.1073/pnas.1002862108
|View full text |Cite
|
Sign up to set email alerts
|

Proline- and acidic amino acid-rich basic leucine zipper proteins modulate peroxisome proliferator-activated receptor α (PPARα) activity

Abstract: In mammals, many aspects of metabolism are under circadian control. At least in part, this regulation is achieved by core-clock or clock-controlled transcription factors whose abundance and/or activity oscillate during the day. The clock-controlled prolineand acidic amino acid-rich domain basic leucine zipper proteins D-site-binding protein, thyrotroph embryonic factor, and hepatic leukemia factor have previously been shown to participate in the circadian control of xenobiotic detoxification in liver and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 52 publications
1
60
0
Order By: Relevance
“…In accordance, liver metabolomics and lipidomics studies reported that free fatty acids and triglycerides accumulate in liver around the same time of the day in a clock-dependent manner (16,19,48). Furthermore, feeding time defines the phase of lipid accumulation in liver (16,37).…”
Section: Discussionmentioning
confidence: 71%
“…In accordance, liver metabolomics and lipidomics studies reported that free fatty acids and triglycerides accumulate in liver around the same time of the day in a clock-dependent manner (16,19,48). Furthermore, feeding time defines the phase of lipid accumulation in liver (16,37).…”
Section: Discussionmentioning
confidence: 71%
“…Altered clock gene expression has recently been implicated in metabolic regulation in the liver (14,20). Since we found altered clock gene expression in all fat pads, we examined whether these genes were also differentially expressed in liver as part of a systemic effect.…”
Section: E216mentioning
confidence: 99%
“…Dbp and Tef are members of the PAR (proline and acidic amino acid-rich) subfamily of basic leucine zipper (bZip) transcription factors together with the third member Hlf (hepatic leukemia factor), which operate as heterodimers (13). These factors have previously been implicated in lipid metabolism in the liver (14), but a function for these genes in preadipocyte recruitment and/or terminal differentiation has not been described. We found reduced expression of Dbp and Tef (variant 2) mRNA in cells treated with differentiation stimuli compared with untreated cells beginning at ϳ16 h after induction (Fig.…”
Section: E216mentioning
confidence: 99%
“…Additionally, Acot genes were also up-regulated after SQ1 treatment. ACOTs are auxiliary enzymes catalyzing the hydrolysis of fatty acylCoAs with suggested roles in regulating intracellular CoA levels and in fatty acid metabolism (Hunt and Alexson, 2008), potentially by generating ligands for PPAR activation (Gachon et al, 2011;Hunt et al, 2014). Many of these changes are consistent with farnesol-derived DCAs undergoing partial oxidation in the peroxisome, producing chain-shortened DCAs that can then either be excreted or further metabolized in the mitochondria (Hiyoshi et al, 2003).…”
Section: Regulation Of Hepatocellular Gene Expression By Isoprenoidsmentioning
confidence: 77%